Palm oil-based polyol for coatings - Siti Irhith Bushrah, Noor Mahadi (2015)
Polyols are widely used in the formulations for polyurethanes. Nowadays, the recent thread of oil price increase has lead government to create the new ideas for polyol production instead of using petroleum. Palm oil (PO) based polyol is an alternative material that may possibly replace petrochemical-based polyol for polyurethane coating material. Polyurethane was synthesized by reacting palm oil-based polyol with isocyanate. The parameters that have been focused throughout this experiment were mol ratio of palm difference weight ratio of hydrogen peroxide for crude palm oil (CPO) to Acetic Acid to H2O2 during epoxidation process, reaction time in opening ring and the ratio polyol to isocyante for coating process .The experiment works has been done at UMP’s basic engineering laboratory. In this study, PO was first epoxidized to form epoxidation of palm oil (EPO). The process has been carried out with 4 samples at difference weight ratio of hydrogen peroxide (H2O2) for CPO to Acetic Acid to H2O2 which are 1:5:1, 1:5:2,1:5:4 and 1:5:6.The presence of oxirane ring of EPO was characterized by Fourier Transform Infrared Spectroscopy (FTIR) and the iodine value of EPO was characterized by Potentiometric Titrator. Then, EPO was converted to palm oil-based polyol by the opening ring reaction with ethyl glycol. The process was carried with difference set of reaction time which is 20 minutes, 40 minutes and 60 minutes respectively. The present of hydroxyl group in polyol was characterized by FTIR and acid value was determined by using Potentiometric Titrator. Palm oil-based polyol was mixed with isocyanate to produce polyurethane coating at different ratio polyol to isocyante were 1:1, 1:2 and 1:3. Scanning Electron Microscopy (SEM) is used in order to analyze the surface structure of coating that form. The results shown that lower iodine value (0.85 I2 g/100g) was obtained by using mol ratio of 1:5:4. At 60 minutes reaction of opening ring showed the present of hydroxyl group at peak 3481 cm-1 and the acid value of polyol that obtain at this condition was 3.86 mg KOH. Based on SEM image, by using the ratio polyol to isocyante of 1:3 shows the effect of isocyante on the bubble size and indicate that the bubble size increase with the increase with isocyate content. Based on study, palm oil was able to produce palm oil-based polyol with the low iodine value, low acid value and low functional group which is suitable to be used in coating applications.